2013
DOI: 10.1039/c3cc39066g
|View full text |Cite
|
Sign up to set email alerts
|

Fluorinated 5- and 7-membered carbacycle motifs by reaction of difluorocarbene with acetylene ethers

Abstract: The reaction of acetylene ethers with difluorocarbene (CF(2)), generated from the Ruppert-Prakash reagent, unexpectedly gave rise to co-produced fluorinated bicyclic [2.1.1]-hex-2-ene and cyclohepta-1,4-diene ring products.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 23 publications
0
17
0
Order By: Relevance
“…2 Recently, conditions were reported that render Me 3 SiCF 3 an excellent source of difluorocarbene (CF 2 ) (eqn (1)), as applied to the synthesis of difluorocyclopropanes and difluorocyclopropenes, 3 as well as unusual fluorinated carbacycle motifs. 4 Iodide activates Me 3 SiCF 3 to liberate the trifluoromethyl anion, which decomposes into CF 2 and F À . The fluoride ion also reacts with Me 3 SiCF 3 to release CF 3 À .…”
mentioning
confidence: 99%
“…2 Recently, conditions were reported that render Me 3 SiCF 3 an excellent source of difluorocarbene (CF 2 ) (eqn (1)), as applied to the synthesis of difluorocyclopropanes and difluorocyclopropenes, 3 as well as unusual fluorinated carbacycle motifs. 4 Iodide activates Me 3 SiCF 3 to liberate the trifluoromethyl anion, which decomposes into CF 2 and F À . The fluoride ion also reacts with Me 3 SiCF 3 to release CF 3 À .…”
mentioning
confidence: 99%
“…A decrease of the amount of 1 from 2.0 to 1.5 equivalents gave a higher yield of 3 a (Condition B). The relatively lower yield of 3 a with 2.0 equivalents of 1 probably arose from the formation of the unstable bicyclobutane through an additional [2+1] cycloaddition 14b. A comparison of the reaction temperatures (Conditions B and C) showed that a high temperature is beneficial for this reaction.…”
Section: Methodsmentioning
confidence: 99%
“…The more common route is difluoromethylation of thiols (Scheme 2a). In this regard, a series of difluoromethylation reagents have been developed in recent years, such as 9 TMSCF 2 Br, 10 TMSCF 2 Cl, 11 TMSCF 3 , 12 ClCF 2 COPh, 13 and PhS(O)(NTs)CF 2 H. 14 is a cumbersome thing, because they are stinky and easy to dimerize. Although disulfides can also be converted to difluoromethylthiolation of (hetero)arenes with TMSCF 2 H, 15 the raw material utilization rate is only half, and the substrate compatibility is not good.…”
Section: (Scheme 1)mentioning
confidence: 99%
“…The more common route is difluoromethylation of thiols (Scheme a). In this regard, a series of difluoromethylation reagents have been developed in recent years, such as HCF 2 Cl, BrCF 2 P­(O)­(OEt) 2 , ClCF 2 CO 2 Na, HCF 2 OTf, TMSCF 2 Br, TMSCF 2 Cl, TMSCF 3 , ClCF 2 COPh, and PhS­(O)­(NTs)­CF 2 H . However, transformation of aryl thiols is a cumbersome thing, because they are stinky and easy to dimerize.…”
mentioning
confidence: 99%